Shavteli Winery: where to go from here?. Issue 4 (27th January 2016) - Gilinsky, Armand; Trela, Brent
Abstract : Title: – Shavteli Winery: where to go from here? Subject area: – International marketing, national competitiveness, strategic decision-making, wine. Study level/applicability: – Undergraduate and MBA. Case overview: – The nationally important Georgian wine industry by 2008 was in a deep recession due largely to the continuing 2006 Russian wine embargo, prior to which Russia had been the largest export market for Georgian wines. Second World War-era Georgian wineries such as Shavteli (disguised), in the historic Racha-Lechkumi wine-producing region, were disadvantaged due to aging facilities, lack of tourist infrastructure, and inadequate capital to make needed changes to compete in the global markets for emerging economy wines. All nearby wineries faced continuing operating deficits, high inventory levels, and could lose much of their aging wine inventory to oxidation if they could not quickly sell more wine or convert the wine to brandy. To avert becoming another defunct producer, Shavteli needed a strategy. Industry observers were divided about whether Shavteli and its sister Georgian wineries should continue operating independently, seek government support, or form a marketing association to create new export demand. Students need to prepare a strategic plan for Shavteli and the Georgian wine industry. Expected learning outcomes: – Students should develop well-supported recommendations for competitive strategies in an emerging economy. Students should use strengths, weaknesses, opportunities, and threats and country competitiveness analyses to ascertain vision and mission, segmentation, targeting, positioning, and alliance strategies for international markets. Supplementary materials: – Teaching notes.